Stability of betacyanin from red pitahaya (Hylocereus polyrhizus) and its potential application as a natural colourant in milk - Gengatharan, A.; Dykes, Gary; Choo, W. (2016)
The effects of temperature (30, 50, 85 and 100 °C) treatment and 10 weeks of refrigerated storage (4 °C) on the betacyanin content and colour stability of betacyanins from red pitahaya (Hylocereus polyrhizus) were investigated and compared to red beet (Beta vulgaris; E-162) which was used as a control. Temperature treatment at 50 and 85 °C caused a greater reduction in betacyanin content (BC) in E-162 compared to red pitahaya by inducing changes in betacyanin profile. The 10 weeks of refrigerated storage at 4 °C induced colour changes in betacyanins from red pitahaya and E-162. In milk, betacyanins from red pitahaya presented a lower loss of BC and total colour changes (ΔE*) compared to E-162. The microbial onset in milk containing betacyanins from red pitahaya and E-162 was delayed up to day 5 of refrigerated storage at 4 °C compared to day 3 in plain milk. Milk containing betacyanins from red pitahaya showed better colour acceptability (3.89 ± 1.89) compared to E-162 (6.10 ± 1.71). Hence, betacyanins from red pitahaya may be a potential natural functional colourant to simulate strawberry colour in milk.